Cancer stem cells CD133 inhibition and cytotoxicity of certain 3-phenylthiazolo[3,2-a]benzimidazoles: design, direct synthesis, crystal study and in vitro biological evaluation - Ghada H. Al-Ansary; Wagdy M. Eldehna; Hazem A. Ghabbour; Sara T. A. Al-Rashood; Khalid A. Al-Rashood; Radwa A. Eladwy; Abdullah Al-Dhfyan; Maha M. Kabil; Hatem A. Abdel-Aziz (Taylor & Francis Group, 2017)
Cancer stem cells (CSCs) have been objects of intensive study since their identification in 1994. Adopting a structural rigidification approach, a novel series of 3-phenylthiazolo[3,2-a]benzimidazoles 4a-d was designed and synthesised, in an attempt to develop potent anticancer agent that can target the bulk of tumour cells and CSCs. The anti-proliferative activity of the synthesised compounds was evaluated against two cell lines, namely; colon cancer HT-29 and triple negative breast cancer MDA-MB-468 cell lines. Also, their inhibitory activity against the cell surface expression of CD133 was examined. In particular, compound 4b emerged as a promising hit molecule as it manifested good antineoplastic potency against both tested cell lines (IC50 = 9 and 12 μM, respectively), beside its ability to inhibit the cell surface expression of CD133 by 50% suggesting a promising potential of effectively controlling the tumour by eradicating the tumour bulk and inhibiting the proliferation of the CSCs. Moreover, compounds 4a and 4c showed moderate activity against HT-29 (IC50 = 21 and 29 μM, respectively) and MDA-MB-468 (IC50 = 23 and 24 μM, respectively) cell lines, while they inhibited the CD133 expression by 14% and 48%, respectively. Finally, a single crystal X-ray diffraction was recorded for compound 4d.